Climatic resilient agriculture for root, tuber, and banana crops using plant growth-promoting microbes - Kaushal, M. (Elsevier, 2019)
Plant growth-promoting microbes function as bacterial inoculants and contribute to the enhancement of agronomic efficacy by lowering production costs and environmental pollution. Interactions between plants and microbes are either antagonistic or synergistic within soil. The efficiency of plant growth-promoting rhizobacteria may vary due to environmental factors and is directly proportional to the growth and yield of plants. Also, constant maintenance of global food security has become a major challenge. Biodiversity is regarded as one of the most effective alternatives for climate change resilient farming systems. Plant growth-promoting microbes also facilitate crop growth under diverse stress conditions and mitigate the long-term impacts of climate change. In the present chapter, the possible intervention of beneficial microbes on climate change in relation to plant growth and yield is reviewed. Focus has been given to the negative pressure applied by climate change on crops grown in sub-Saharan Africa and possible remedies for this using beneficial microbial strains.